Determinants of China's development assistance for health at the sub-national level of African countries (2006-2015) - Hao-min Yang; Pei-long Liu; Yan Guo (BMC, 2018)
Abstract Background Despite the increasing interest in China's development assistance for health (DAH) in African countries, little is known regarding the distribution and determinants of China's DAH project allocation among the principle subdivisions (provinces & states) within African countries. Methods We mapped the distribution of China's DAH projects in 670 principle subdivisions of 50 African countries during 2006-2015 using web-based information. The political, demographic, health and socioeconomic indicators of DAH allocation were analyzed using conditional logistic regression models. The national capital city and political leader's birth place were selected as the main political indicators, and health indicators were selected according to different fields of the DAH projects. Results China's DAH projects (mainly China medical teams [CMTs], hospitals and anti-malaria centers) were mostly allocated to the western and eastern coasts of Africa, although CMTs were also dispatched to northern Africa. National capital cities were significantly associated with the allocation of China's DAH projects (P <  0.001). Anti-malaria centers were more likely to be allocated to principle subdivisions with larger populations (OR = 1.35), and CMTs were allocated to subdivisions with high population densities (OR = 79.01). No health-related indicators were identified to affect project allocation except for the facility delivery rate and under-five mortality rate, which were associated with hospital allocation. We also found an association between CMT allocation and the use of artemisinin-based combination therapy in children. Conclusions Allocation of China's DAH projects is strongly affected by political and demographic factors. Implementation of China's new DAH projects should target health and socio-economic indicators and impact metrics in scaling up tailored and cost-effective programs in Africa.